CR-POSSUM and Surgical Apgar Score as predictive factors for patients' allocation after colorectal surgery - Pinho,Sílvia (2018)
Abstract Background and objectives Surgical patients frequently require admission in high-dependency units or intensive care units. Resources are scarce and there are no universally accepted admission criteria, so patients' allocation must be optimized. The purpose of this study was to investigate the relationship between postoperative destination of patients submitted to colorectal surgery and the scores ColoRectal Physiological and Operative Severity Score for the enUmeration of Mortality and Morbidity (CR-POSSUM) and Surgical Apgar Score (SAS) and, secondarily find cut-offs to aid this allocation. Methods A cross-sectional prospective observational study, including all adult patients undergoing colorectal surgery during a 2 years period. Data collected from the electronic clinical process and anesthesia records. Results A total of 358 patients were included. Median score for SAS was 8 and CR-POSSUM had a median mortality probability of 4.5%. Immediate admission on high-dependency units/intensive care units occurred in 51 patients and late admission in 18. Scores from ward and high-dependency units/intensive care units patients were statistically different (SAS: 8 vs. 7, p < 0.001; CR-POSSUM: 4.4% vs. 15.9%, p < 0.001). Both scores were found to be predictors of immediate postoperative destination (p < 0.001). Concerning immediate high-dependency units/intensive care units admission, CR-POSSUM showed a strong association (AUC 0.78, p = 0.034) with a ≥9.16 cut-off point (sensitivity: 62.5%; specificity: 75.2%), outperforming SAS (AUC 0.67, p = 0.048), with a ≤7 cut-off point (sensitivity: 67.3%; specificity: 56.1%). Conclusions Both CR-POSSUM and SAS were associated with the clinical decision to admit a patient to the high-dependency units/intensive care units immediately after surgery. CR-POSSUM alone showed a better discriminative capacity.